Green amorphous nanoplex as a new supersaturating drug delivery system - Cheow, Wean Sin (2013)
The nanoscale formulation of amorphous drugs represents a highly viable supersaturating drug-delivery system for enhancing the bioavailability of poorly soluble drugs. Herein we present a new formulation of a nanoscale amorphous drug in the form of a drug–polyelectrolyte nanoparticle complex (or nanoplex), where the nanoplex is held together by the combination of a drug–polyelectrolyte electrostatic interaction and an interdrug hydrophobic interaction. The nanoplex is prepared by a truly simple, green process that involves the ambient mixing of drug and polyelectrolyte (PE) solutions in the presence of salt. Nanoplexes of poorly soluble acidic (i.e., ibuprofen and curcumin) and basic (i.e., ciprofloxacin) drugs are successfully prepared using biocompatible poly(allylamine hydrochloride) and dextran sulfate as the PE, respectively. The roles of salt, drug, and PE in nanoplex formation are examined from ternary phase diagrams of the drug–PE complex, from which the importance of the drug’s charge density and hydrophobicity, as well as the PE ionization at different pH values, is recognized. Under the optimal conditions, the three nanoplexes exhibit high drug loadings of 80–85% owing to the high drug complexation efficiency ( 90–96%), which is achieved by keeping the feed charge ratio of the drug to PE below unity (i.e., excess PE). The nanoplex sizes are 300–500 nm depending on the drug hydrophobicity. The nanoplex powders remain amorphous after 1 month of storage, indicating the high stability owed to the PE’s high glass-transition temperature. FT-IR analysis shows that functional groups of the drug are conserved upon complexation. The nanoplexes are capable of generating prolonged supersaturation upon dissolution with precipitation inhibitors. The supersaturation level depends on the saturation solubility of the native drugs, where the lower the saturation solubility, the higher the supersaturation level. The solubility of curcumin as the least-soluble drug is magnified 9-fold upon its transformation to the nanoplex, and the supersaturated condition is maintained for 5 h.